(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The utilization of cottonseed meal (CSM) as a protein supplement in poultry diets is hindered by the presence of gossypol which can adversely affect growth performance and increase mortality in broilers. This study investigated the impact of CSM supplemented with phytase on growth, performance, and hematological parameters in Arbor Acre broiler chickens. A total of 216 day-old broiler chickens were utilized in the experiment, starter diets was provided until day 20 and thereafter experimental diets from days 21 to 28. Six semi-purified diets were formulated in a 3x2 factorial, varying in CSM content (150, 300, and 450g/kg) and phytase supplementation (0 or 1000 units of Natuphos). Feed intake, body weight, and weight gain were monitored, while blood samples were collected for hematological analysis. There were no significant differences (P>0.05) in feed intake, final weight, and weight gain among treatment groups with or without phytase supplementation, however average feed intake per bird across the treatments ranged from 219.80 to 278.00g, while a range of 204.30 to 259.00g was observed for average dry matter intake per bird. Hematological parameters including erythrocytes, hemoglobin, packed cell volume, lymphocytes, heterocytes, basophil, eosinophils were within the normal range and did not differ significantly between birds fed diets with or without phytase supplementation. The inclusion of phytase in broiler diets showed no adverse effects on blood parameters and improved growth performance. Overall, these findings suggest that phytase supplementation in broiler diets containing CSM could be beneficial for growth performance without impacting blood parameters during short-term feeding periods.